Profitability and Remuneration in the UK banking industry - Bai, Renyuan (2016)
This dissertation tries to examine the determinants of the profitability in the UK banking industry and the pay-performance relationship during the period of 2006-2015. The empirical findings indicate that some variables from common, bank-specific and macroeconomic categories have statistically significant influence on the bank profitability. However, when linking remuneration and bank profitability together, no significant relationship can be found. Later case study on bonuses and bank profitability show a significant relationship exists. The inclusion of diverse variables as well as additional case studies can help us to gain the new insights into what determinants the profitability of the UK banking industry and the pay-performance relationship.